Benchmarking QSP Models Against Simple Models: A Path to Improved Comprehension and Predictive Performance. (22nd August 2018) - Stein, Andrew M.; Looby, Michael
Abstract : Quantitative Systems Pharmacology (QSP) models provide a means of integrating knowledge into a quantitative framework and, ideally, this integration leads to a better understanding of biology and better predictions of new experiments and clinical trials. In practice, these goals may be compromised by model complexity and uncertainty. To address these problems, we recommend that the predictive performance of QSP models be assessed through comparison with simpler models developed specifically for this purpose.